Leadership of School Principles in The Digital Era in Building Innoving Teacher Character HR - Khoirul Anwar; Choeroni; Pandu Adi Cakranegara; Susilo Surahman; Ade Risna Sari (PT ARRUS Intelektual Indonesia, 2022)
This research examines how the leadership of the principal is in its efforts to build teachers who are characterized and innovative in this Digitalization Era. The research used in this research is a qualitative research which is described descriptively. Various sources were processed in this study such as books, research results, journals, and research articles. The results of this study suggest that over the last decade, studies of the effects of school leadership have increasingly aimed at identifying and validating the pathways through which principal leadership impacts key teaching and learning processes in schools. In addition, it was found that digital technology provides new challenges in the world of education today. Innovation is needed especially for school principals as leaders in the school sector to realize the various aspirations of the nation's education. One aspect that needs to be realized is creating human resources, namely teachers who have high character and innovation through the leadership of the school principal in this digital era. The role of the principal in this case is very important given the strategic position he holds. Through role models and strategic solutions, both traditional, interpersonal, and HR development, it is expected to be able to motivate teachers to be more creative and innovative in the teaching and learning process.